The modern problem state of the autonomic dysfunction of heard in children - O. B. Doronina; L. A. Voropai; N. G. Voropai (Бюллетень сибирской медицины)
Autonomic dysfunction of cardiovascular system in children and teenagers is described. The main causes of the arterial hypertension are found out, the importance of division of arterial hypertension on the primary and secondary is emphasized. Arterial hypertension in examined children is accompanied of syncope states, difference kind of arhythmias and heart conductibility. The syndrome of dysplasia of connective tissue was found out in these patients with arterial hypertension more often.